Analysis and Characterization of Interactions Between Components in Claymask Formulations - Khairatun Annisa; Ahmad Nasir Pulungan; Junifa Layla Sihombing (Universitas Negeri Medan, 2025)
The basic properties that need to be considered and maintained in the use of an ingredient in cosmetic and pharmaceutical formulations are: colloidal size, plasticity of crystal structure, mineralographic composition, high cation exchange capacity, development capacity, high specific surface area, and consequently strong adsorption and absorption capacity. Clay masks can contain active ingredients in the form of antibacterial with alternative natural ingredients such as babadotan leaf extract. The analysis of the functional cluster in the study was obtained using the Fourier Transform Infrared (FT-IR) method,Evaluation of clay mask preparations includes testing of physical and chemical properties. Testing of physicochemical properties consists of organoleptics, pH, homogeneity, dispersibility, adhesion and antibacterial test against bacteria p. Acnes. The stability of the preparation will be damaged if the mixing system is disturbed, mainly due to temperature changes and changes in composition due to excessive addition of one of the phases or if the emulsifying substances are not mixed with each other. The extraction results obtained from babadotan the yield produced is 17.63%. The FTIR spectrum obtained for the clay mask formulation shows the presence of new peaks at wave numbers 3310, 2120, 1430 and 2126 cm-1 where these peaks appear due to the additional ingredients used in the cosmetic formulation.The interaction between the components of the clay mask depends on the type of clay being applied. Interactions can be seen in FTIR with additional spectral peaks caused by other additives such as glycerin, In which the interaction shows the OH group involved in water absorption. This is because the results of all evaluations, Formula I tends to be stable close to the requirements of the clay mask preparation.